(untitled) (Global Journal of Medical Research, 2014)
TTP is a very uncommon disease which used to have very high mortality and morbidity before the introduction of plasmapharesis and immunosup-pressant therapy. Even after the introduction of these modalities, atypical HUS patients had a very grave prognosis and ultimately led to death in many until the introduction of complement inhibitors like eculizumab which is C5a monoclonal antibody. Additionally differentiating typical HUS versus atypical HUS was very difficult but some work on complement markers can be very fruitful in differentiating them.